Studi Sistem Drainase Jalan Beliang Kota Palangka Raya - Novrianti Novrianti (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
At this time the drainage conditions are channeled to the primary channel that leads to the river, using land use, making the recharge less and less. By paying attention to the floods in 2015 and several years, to find out, the research conducted on the Jalan Beliang Drainage Study System in Palangka Raya City. This study aims to find out the existing drainage systems and channels and knowing between rational debit (Qr) and channel debit (Qs) in the study area. Based on field data, the base width (b) varies between 0.16 m - 0.75 m, and the depth is between 0.35 m - 0.75 m. Results from the garuda XA area indicate that Qr